Gender novelty and personalized news coverage in Australia and Canada. Issue 2 (March 2021) - Trimble, Linda; Curtin, Jennifer; Wagner, Angelia; Auer, Meagan; Woodman, V K G; Owens, Bethan
Are female government leaders more likely than their male counterparts to see their gendered identities and personal lives profiled in news coverage of their ascents? Are non-novel women leaders—those who are the second in their jurisdiction to achieve the top political job—less likely to experience media personalization than did the women who preceded them in office? By analyzing newspaper coverage of 20 Australian and Canadian premiers, ten women and their immediate male predecessors, our study establishes that female premiers were more extensively personalized in news coverage than were male premiers, particularly in the Australian context. However, gender novelty and other factors proved significant. The proposition that an increased presence of women in leadership roles diminishes the salience of private lives and personal characteristics is supported by our study, suggesting that gender stereotyping of female political leaders will decrease over time as more women exercise political power.